Propensity to Support Sustainability Initiatives: A Cross-National Model - Parboteeah, K. Praveen; Addae, Helena M.; Cullen, John B. (2012)
Businesses and the social sciences are increasingly facing calls to further scholarship dedicated to understand sustainability. Furthermore, multinationals are also facing similar calls given their high profile and their role in environmental degradation. However, a literature review shows that there is very limited understanding of sustainability at a cross-national level. Given the above gaps, we contribute to the literature by examining how selected GLOBE [House et al., Culture, leadership and organizations: The GOBE study of 62 societies. Sage Publications, Thousand Oaks, 2004] cultural dimensions are related to individuals’ propensity to support sustainability initiatives in 33 countries. We use data from the World Values Survey [World Values Study Group, World Values Surveys and European Value Surveys, 1999–2001. Inter-University Consortium for Political and Social Research, Ann Arbor, 2004] and test our hypotheses using Hierarchical Linear Modeling (HLM). Results support all but one hypothesis. Specifically, uncertainty avoidance is not related to propensity to support sustainability initiatives. In contrast, performance orientation and assertiveness have the desired negative relationship with our dependent variable while collectivism, future orientation, and human orientation have the desired positive relationship. We discuss the conceptual and practical implications of this study.
Keywords: GLOBE cultural scheme; Cross-national; Sustainability